1995
DOI: 10.1177/088307389501000417
|View full text |Cite
|
Sign up to set email alerts
|

Serial CT Scanning in Childhood Tuberculous Meningitis: Prognostic Features in 198 Cases

Abstract: Serial cranial computed tomographic (CT) scanning and intracranial pressure monitoring were performed on 198 children with stage II and III tuberculous meningitis. The aims of the study were to document the course of tuberculous hydrocephalus during medical and surgical treatment, as well as the prognostic significance of parenchymal changes in the brain as demonstrated by CT. Lumbar cerebrospinal fluid pressure was monitored continuously for a 1-hour period in all patients on admission and at weekly intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 18 publications
4
43
1
4
Order By: Relevance
“…In a recent longitudinal study on CT scanning in childhood TBM, evidence was found of an ongoing inflammatory process [15]. Increasing basal enhancement (28% of patients) and new infarcts, probably due to progressive vasculitis (22% of patients), were evident on the CT scan after the 1st month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent longitudinal study on CT scanning in childhood TBM, evidence was found of an ongoing inflammatory process [15]. Increasing basal enhancement (28% of patients) and new infarcts, probably due to progressive vasculitis (22% of patients), were evident on the CT scan after the 1st month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,16 CT helps in recognising features suggestive of CNS tuberculosis like basal enhancement, tuberculoma and identifying complications of TBM including infarction and hydrocephalus. 8,17,18,19 The common triad of CT findings in TBM are:…”
Section: Discussionmentioning
confidence: 99%
“…6 As delay in diagnosis and treatment leads to greater morbidity and mortality, the emphasis should be on early diagnosis of neurotuberculosis. 7,8 The role of CT in early diagnosis of TBM and its complications is well established. 8,9,10 It is valuable in identifying intracranial lesions which are characteristic of neurotuberculosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral infarctions are reported in up to one-third or more of patients with TBM, resulting in deficits such as hemoparesis, monoparesis, aphasia, cognitive impairment, visual field deficits, movement disorders, ataxia, brain stem syndromes, etc. [1,2]. In a CT study of 198 patients with TBM, basal ganglia infarcts were present at admission in 31% [1].…”
Section: Introductionmentioning
confidence: 96%